ADHD and autism among nurses - Hedlund, Åsa (University of Gävle, 2026)
The quantitative dataset and the qualitative interview material were generated within a research project in nursing science focusing on health and well-being at work among nurses with autism and/or ADHD. The data material consists of survey and interview data covering health, well-being, organizational and social work environment, as well as autism and ADHD “symptoms.” Background variables include, among others, diagnosis, age, and gender. Survey data were collected through web-based questionnaires distributed via social media. The dataset consists of a cleaned CSV file and an SAV file. No specific software is required to use the data beyond standard programs capable of reading CSV files. The interview data consist of text documents from individual oral interviews, saved in DOCX format.

Det kvantitativa datasetet och det kvalitativa intervjumaterialet har genererats inom ett forskningsprojekt i vårdvetenskap med fokus på hälsa och välbefinnande i arbetet hos sjuksköterskor med autism och/eller ADHD. Datamaterialet består av enkät- och intervjudata som omfattar hälsa, välbefinnande, organisatorisk och social arbetsmiljö samt autism- och ADHD-"symtom". Bakgrundsvariabler inkluderar bland annat diagnos, ålder och kön. Enkätata har samlats in genom webbaserade enkäter som distribuerats via sociala medier. Datasetet består av en rensad CSV-fil och en SAV-fil. Ingen särskild programvara krävs för att använda data utöver standardprogram som kan läsa CSV-filer. Intervjudata består av textdokument från muntliga enskilda intervjuer, sparade i docx.
ADHD och autism hos sjuksköterskor
Keywords: Occupational Health; Arbetshälsa; Attention Deficit Disorder with Hyperactivity; ADHD; Autistic Disorder; Autism; Health Personnel; Hälso- och sjukvårdspersonal; Nurses; Sjuksköterskor; ADHD; ADHD; Nursing; Omvårdnad